2020
DOI: 10.1111/nph.16789
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community structure of ericoid mycorrhizal fungi in European bogs and heathlands across a gradient of nitrogen deposition

Abstract: Summary Despite the ecological significance of ericoid mycorrhizal fungi, little is known about the abiotic and biotic factors driving their diversity and community composition. To determine the relative importance of abiotic and biotic filtering in structuring ericoid mycorrhizal fungal communities, we established 156 sampling plots in two highly contrasting environments but dominated by the same Ericaceae plant species: waterlogged bogs and dry heathlands. Plots were located across 25 bogs and 27 dry heath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 60 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, our expectation concurs with Van Geel et al. (2020) who showed that soil phosphorus content was negatively related to ERM fungal richness in European bogs. Taken together, changes in belowground shrub dynamics in the warmest enclosure may lead to a decline in peat accumulation, at least as facilitated by fungal interactions because of the increase in ericaceous shrub root abundance and the loss of ERM fungi that produce necromass known to be highly recalcitrant (Clemmensen et al., 2015; Fernandez et al., 2019; Thormann, 2006) and that potentially produce mycelial networks (Grelet et al., 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our expectation concurs with Van Geel et al. (2020) who showed that soil phosphorus content was negatively related to ERM fungal richness in European bogs. Taken together, changes in belowground shrub dynamics in the warmest enclosure may lead to a decline in peat accumulation, at least as facilitated by fungal interactions because of the increase in ericaceous shrub root abundance and the loss of ERM fungi that produce necromass known to be highly recalcitrant (Clemmensen et al., 2015; Fernandez et al., 2019; Thormann, 2006) and that potentially produce mycelial networks (Grelet et al., 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Instead, fertilizer addition may cause the host plant to reallocate resources (i.e., carbon-rich photosynthates) away from root-associated symbionts (Olsson, Rahm and Aliasgharzad 2010;Kiers et al 2011;Konvalinková et al 2017), resulting in reduced fungal richness and diversity in the rhizosphere. This possibility could have significant implications for stability of ERM symbioses in the context of anthropogenic nutrient deposition in the nutrientpoor habitats where ericaceous plant often thrive (Van Geel et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the relative availability of limiting nutrients in soil, P as well as N, may influence ericaceous plant-fungal interactions and ErMF community composition (Hazard et al 2014;Van Geel et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, reduced growth rates and biomass were detected under increasing N deposition for both ectomycorrhizal fungi (Bahr et al, 2013;de Witte et al, 2017;Kjøller et al, 2012;Nilsson et al, 2007;Ostonen et al, 2011) and arbuscular mycorrhizal fungi (Nilsson et al, 2007). Mycorrhizal fungal diversity and species richness tends to decline with increasing N deposition (Ceulemans et al, 2019;de Witte et al, 2017;Lilleskov et al, 2002;Suz et al, 2014;van Geel et al, 2020), and shifts in fungal community composition along N deposition gradients have been detected (Andrew et al, 2018;Jarvis et al, 2013;Lilleskov et al, 2008Lilleskov et al, , 2002Moore et al, 2021). There are few studies on litter decomposition along N deposition gradients, a process that is strongly determined by fungal activity.…”
Section: Learning From N Deposition Gradientsmentioning
confidence: 99%